Artificial Intelligence in Healthcare: Opportunities, Challenges, and Ethical Considerations - Purwoko, Reza Yuridian; Alfaqih, Muhammad Subhan (IT for Society, 2024)
Artificial Intelligence (AI) has emerged as a transformative force in healthcare, offering innovative solutions for diagnostics, treatment planning, and patient monitoring. This paper explores the current state of AI applications in health, focusing on its potential to improve patient outcomes, enhance healthcare delivery, and address ethical and governance challenges. Drawing from a comprehensive review of recent literature and case studies, we discuss the role of AI in areas such as medical imaging, predictive analytics, personalized medicine, and public health surveillance. We also highlight the importance of ethical considerations, data privacy, and the need for international collaboration in AI governance. The paper concludes with recommendations for future research and policy development to ensure the responsible and effective use of AI in healthcare.